2020
DOI: 10.3390/su12114692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land Use/Land Cover on Surface-Water Quality of Santa Lucía River, Uruguay

Abstract: Land use/land cover is one of the critical factors that affects surface-water quality at catchment scale. Effective mitigation strategies require an in-depth understanding of the leading causes of water pollution to improve community well-being and ecosystem health. The main aim of this study is to assess the relationship between land use/land cover and biophysical and chemical water-quality parameters in the Santa Lucía catchment (Uruguay, South America). The Santa Lucía river is the primary potable source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Field agriculture is a significant land use in many areas of the world and has been documented as a contributor of non-point source pollution to surface waters. In a recent study in Uruguay, [1] researchers found a strong correlation between total phosphorus (P) and agriculture land use in a river. In central Asia, remote sensing was used to analyze effects of land use on surface water contamination [2].…”
Section: Introductionmentioning
confidence: 99%
“…Field agriculture is a significant land use in many areas of the world and has been documented as a contributor of non-point source pollution to surface waters. In a recent study in Uruguay, [1] researchers found a strong correlation between total phosphorus (P) and agriculture land use in a river. In central Asia, remote sensing was used to analyze effects of land use on surface water contamination [2].…”
Section: Introductionmentioning
confidence: 99%
“…Uruguay has a humid subtropical climate (Cfa, according to the Köppen climate classification) with a mean temperature in the warmest month equal to 22 • C or higher [18]. The study area is characterized by total annual precipitation that varies between 1000 mm and 1500 mm and a temperature that can vary between 3 • C and 30 • C [19]. The region has a landscape of smooth hills with an average slope equal to 2.68%.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…Both groups of techniques belong to the family of unsupervised methods, where information about other response variables or group belonging is not used to obtain results. This makes these techniques suitable for exploratory analysis, where the main aim is hypothesis generation rather than hypothesis verification [5,46].…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…It is generated from surface water bodies, which provide drinking water, preserve biodiversity, control climate, and maintain phosphorus and nitrate cycling [1]. However, in recent decades, the quality of these water bodies has been threatened by anthropogenic activities (e.g., urbanization, agriculture, water extraction, sewage discharge) [2][3][4][5]. Therefore, in the management plan of pollution control at a watershed scale, a worthwhile initial step is the identification of the pollution sources.…”
Section: Introductionmentioning
confidence: 99%